Intraoperative ultrasonography of liver, bile ducts and pancreas - Cerri, Luciana Mendes de Oliveira; Cerri, Giovanni Guido (São Paulo Medical Journal, 1996)
The use of intraoperative ultrasonography (IOUS) to evaluate liver, bile ducts and pancreatic disease, as compared to the results of preoperative ultrasonography and CT, is discussed. Forty-two patients who underwent abdominal surgery for suspected hepatobiliary and/or pancreatic disease were studied. The intraoperative study was carried out with a portable apparatus (Aloka 500, Japan), using 5.0 MHz and 7.5 MHz linear sterile transducers. The main indications for IOUS were the search for and/or evaluation of primary hepatic masses,hepatic abscesses or metastases, obstructive jaundice, or neuroendocrine tumors. In 15 cases (38.5 percent) from the hepatobiliary group and in 7 cases (58.3 percent) from the pancreatic group, a difference between preoperative and intraoperative findings was observed. The main difference was observed in relation to the number and size of hepatic and pancreatic lesions. The relationship between the lesions and the vascular structures was evaluated through IOUS. The method was also used to guide surgical procedures such as biopsies, the alcoholization of nodules, and the drainage of abscesses. IOUS plays an important role in detecting small hepatic and pancreatic nodules, in the assessment of anatomical relationships between the lesions and the vascular structures, and in the performance of interventionist procedures.